Organosilicon chemistry : novel approaches and reactions - Hiyama, Tamejiro, 1946-; Oestreich, Martin (Wiley-VCH, 2019)
"Provides a unique summary of important catalytic reactions in the presence of silicon. A must-have for all synthetic chemists, this book summarizes all of the important developments in the application of organosilicon compounds in organic synthesis and catalysis. Edited by two world leaders in the field, it describes different approaches and covers a broad range of reactions, e.g. catalytic generation of silicon nucleophiles, Si-H Bond activation, C-H bond silylation, silicon-based cross-coupling reactions, and hydrosilylation in the presence of earth-abundant metals. In addition to the topics covered above, Organosilicon Chemistry: Novel Approaches and Reactions features chapters that look at Lewis base activation of silicon Lewis acids, silylenes as ligands in catalysis, and chiral silicon molecules." --